A conceptual model for clinical psychomotor skill development in an era of simulated and virtual reality. (26th June 2021) - Perry, Suzanne; Bridges, Susan M.; Burrow, Michael F.
Abstract: Psychomotor skill development is central to a beginner practitioner's learning pathway. Curriculum constraints around time, access to facilities and resources in health professions education have prompted the growth in alternative approaches to clinical skill development in both simulation and direct patient care. Among these is the increased incorporation of virtual reality (VR) systems with haptic feedback alongside traditional, solid simulations. Given the rapid growth in the adoption of technological affordances to support skill development, it is cogent to pause and examine whether the underpinning concepts regarding psychomotor skill development that have driven much of the approaches to teach clinical skill acquisition in dentistry remain fit‐for‐purpose. This conceptual paper proposes a new taxonomy for clinical simulation psychomotor skill development in the era of increasing variety of simulation modalities.